El acceso legal al agua, como recurso vital en el sector rural del cantón San Miguel de Bolívar. - Gaibor Guamán, Brayan Darío (2023)
Through this document, an analysis of the activities that will be carried out in the investigation entitled: “Legal access to water, as a vital resource in the rural sector of the San Miguel de Bolívar canton will be carried out. In a legal way, respecting basic and essential parameters, for its normal use and exploitation. The need for this work arises from the population problems of the communities in the rural sector, in the taking of water resources as sources of supply to be used as: watering hole for animals, irrigation of crops, safe and appropriate human consumption, etc. Its legalization is essential not only to determine which sectors are most vulnerable, but also to educate communities and the rural sector in general about legal access to the vital resource of water. To carry out this research, a qualitative methodological approach was selected. Due to the fact that a study will be carried out with the character of analysis and interpretation of the regulations regarding legal access to water. According to the nature of the chosen topic, the methods, types, research techniques have been selected based on a theoretical, legal and doctrinal analysis. Being a documentary investigation, a descriptive, non-experimental, deductive and transversal investigation will be used. The total population considered in this research is 30 inhabitants, who are between the ages of 18 and 65 and are heads of household. From the Balsapamba, Bilován, Regulo De Mora, San Pablo, Santiago, San Vicente margparishes. The techniques to be applied in this research are: a survey and an interview. To do this, a closed questionnaire with alternative questions is used as a data collection instrument. In order to know the reality of legal access to water. In this way it will be possible to establish whether this fundamental right is fulfilled in the rural sectors of the San Miguel canton. Vital Resource, Legal Access, Rural Sector, Water Resources, Water. Keywords: Vital Resource, Legal Access, Rural Sector, Resources, Vital Liquid.